(3OjhGf CHj GSMGb GdZRi GdcdHi GdGTgHis - (3GdZRj , EHQGgje Hf YKeGf Hf eMeO GdcdHj GdGTgHj, CHh ESMGb CHh YKeGf,J (B524 (3g` s ((3eMeO Hf CMeO GdeYQha HGHf LOi s)
(3ChdgG (B:s
(3CeG HYO MeOkG ddg GdhGLH aEf GdTYQ RHOI GdGOH hejOGf GdYQH ceG fhGai LGgdjJge jYXehfg s
(3BNQgG (B:s
(3hcja jNai hdf JNai efGbHce s
(3HChdg JQLeI dUGMH GdOjhGfs
(3HChdg JedcGJ cJH gPG GdcJGH Hf Ydi Hf eMeO Hf eMehO GdTgjQ HGHf GdWhjd GdejOGfi GdOeTbis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B44s
(3eUOQ GbJfGA GdCUd (B:s
(3YGQa MceJ (B((3OhGhjf (B513) s
Keywords: (3eJaQbGJs